Intentional endometrial injury increases embryo implantation potentials through enhanced endometrial angiogenesis. Issue 2 (21st September 2018) - Yang, Jehn-Hsiahn; Chen, Chin-Der; Chou, Chia-Hung; Wen, Wen-Fen; Tsao, Po-Nien; Lee, Hsinyu; Chen, Shee-Uan
Abstract: Embryo implantation rates have been found to be enhanced by precedent endometrial injuries, but the underlying mechanism is not fully investigated. Endometrial inflammation occurs both at peri-implantation period and after endometrial injury, in which vascular reaction is a distinctive feature of inflammation. In this study, intentional endometrial injury was done with a 0.7-mm-diameter brush inserted into the left uterine horn of female ICR mice, then turned around 720° (group 2), and the right uterine horn served as the controls without endometrial injuries (group 1). Intraperitoneal equine chorionic gonadotropin 2.5 IU was injected, followed by human chorionic gonadotropin 10 IU injection, and the uterus was dissected 5 days later, roughly at the peri-implantation period. The peri-implantation endometrium was obtained, and angiogenesis protein array revealed that matrix metalloproteinase-3 (MMP-3), plasminogen activator inhibitor-1 (PAI-1), insulin-like growth factor binding protein 1 (IGFBP-1), and IL-1α were more strongly expressed in injured endometrium (group 2) than in the controls (group 1). Immunohistochemical CD34 staining was more prominently expressed in group 2 uterus, and the treatment with LY294002, a p hosphoinositide 3-kinase (PI3K) inhibitor, significantly decreased CD34 immunopositive cells. The capabilities of permeability, proliferation, tube formation, and migration of mouse endometrial endothelial cells were significantly enhanced in group 2 than in group 1. Our results demonstrate that enhanced endometrial angiogenesis is a possible mechanism accounting for the increased endometrial receptivity after endometrial injury. Abstract : Increased endometrial receptivity after intentional injury is probably due to enhanced endometrial angiogenesis.